Hyperparathyroidism: Unusual location of brown tumors. Issue 2 (3rd February 2022) - Fazaa, Alia; Makhlouf, Yasmine; Miladi, Soussen; Sellami, Mariem; Ouenniche, Kmar; Souebni, Leila; Kassab, Selma; Chekili, Selma; Ben Abdelghani, Kawther; Laatar, Ahmed
Abstract: Brown tumors (BTs) are due to a proliferation of multinucleated giant cells in osteolytic lesions. They complicate the course of hyperparathyroidism. Thanks to an early screening of bone metabolism disorders; BTs are nowadays rare bone manifestations. We demonstrate through these two cases reports unusual locations of BTs in hyperparathyroidism. Abstract : Thanks to early screening; brown tumors rarely reveal hyperparathyroidism. Multiple brown tumors may have a pseudometastatic appearance that can be misleading, especially when it is the first manifestation of the disease. The treatment of brown tumors is based on the management of the underlying etiology. However, in some cases, the curettage of the lesion is necessary.